ANALISIS STABILITAS MENGGUNAKAN MODEL MATERIAL PERALIHAN TANAH-BATUAN - Agung, Putera; A, Ardianto (Politeknik Negeri Jakarta, 2019)
AbstractAn analysis of stability needs to predict stress-strain values of soil, rock, and/or intermediate material (soil-rock) layers around the gate shaft during excavation works. Selection of stress-strain of intermediate material foccused on this paper will affect to the analysis result. This analysis concerned on some consideration to the selection the stress-strain parameters in determination of c’ and f’ parameters. In excavation works,the parameters were applied to the stability analysis of gate shaft construction of dam construction. The stability analysis used a 2 D software of PLAXIS. Each condition of gate shaft was reinforcement and un-reinforcement wall types. From several analyses, the parameters of c’ and f’ from stress-strain of soil was smaller than intermediate material.Keywords: Cohesion; angle of internal friction, stress, strain, gate shaft.Abstrak Suatu analisis stabilitas perlu untuk memperkirakan besarnya tegangan-regangan tanah, batuan, dan atau lapisan material peralihan tanah-batuan (intermediate material) di sekitar lubang galian vertikal. Pemilihan tegangan-regangan dari material peralihan tanah-batuan yang difokuskan pada paper ini akan berpengaruh terhadap hasil analisis. Analisis ini memusatkan perhatian pada beberapa pertimbangan pemilihan parameter tegangan-regangan dalam analisis stabilitas saluran pengalihn vertikal pada konstruksi dam. Analisis stabilitas ini menggunakan software Plaxis 2 D (dimensi). Masing-masing tipe dinding saluran vertikal ini adalah dengan dan tanpa perkuatan tulangan. Dari beberapa analisis, parameter c’ dan f’ dari tanah adalah lebih kecil dari material peralihan. Katakunci: Kohesi, sudut geser dalam, tegangan, regangan, saluran pengalihan vertikal.